Penanaman Kesadaran Budaya Mutu pada Siswa SMK - K.A. Rahman; Mohamad Muspawi; Mulyadi Mulyadi; Sri Rahmah Ramadhoni; Sahrizal Vahlefi (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2024)
Lack of Student Understanding of Quality Culture and Limited Information about Quality Culture available, makes it important for this service to increase student understanding of the importance of awareness of Quality Culture that will encourage massive contributions from all students to create quality schools that are in accordance with student potential. The method is aligned with the principles of developmental psychology, namely identification of needs, preparation of materials, implementation, evaluation, and follow-up. As a result, students are more open-minded to be able to understand quality and develop school quality starting from the development of their own potential.